A relação entre o helicobacter pylori e as pequenas epitelizações colunares do esôfago distal com ou sem metaplasia intestinal - Degiovani, Matheus (2019)
Introduction: The presence of intestinal metaplasia in the distal esophagus (Barrett's esophagus) is an important precursor of adenocarcinoma. Knowledge of the risk factors and the process by which the Barrett develops is very importance and H.pylori can contribute to this development. Objective: To analyze the impact of H. pylori in the gastric mucosa of intestinal metaplasia in the distal esophagus in areas of columnar epithelialization smaller than 10 mm in length, stratified for gender and age. Method: A retrospective study in which were included 373 consecutive patients diagnosed with columnar epithelium in the distal esophagus. In all it was searched the H.pylori by two methods (urease and histology) and applied the inclusion and exclusion factors. It is divided into two groups: the first adding patients without histological diagnosis of Barrett's esophagus (235-63%) and the second comprising the histologically diagnosed with Barrett's esophagus (138-37%). Results: There was no significant difference between the carriers of H. pylori or not in relation to the likelihood of having intestinal metaplasia (p = 0.587). When related to the general group, there was an inverse association between the bacteria and the columnar epithelialization in the distal esophagus. Age (p = 0.031), gender (p = 0.013) and H. pylori (p = 0.613) when connected together to intestinal metaplasia showed no significant relationship. In isolation; when related age and gender, regardless of H. pylori emerged results confirming that older patients and women have a higher incidence of intestinal metaplasia (Barrett's esophagus). Conclusion: The presence or absence of intestinal metaplasia of distal esophagus when related to H. pylori in the gastric mucosa, is not significant. In relation to age and gender, regardless of H.pylori, we note that in women and the greater the age of the individuals, there is an increase in the number of cases with intestinal metaplasia in the distal esophagus.